2013
DOI: 10.1016/j.actbio.2012.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bone regeneration in implants composed of hollow HA microspheres loaded with transforming growth factor β1 in a rat calvarial defect model

Abstract: Implants that serve simultaneously as an osteoconductive matrix and as a device for local growth factor delivery may be required for optimal bone regeneration in some applications. In the present study, hollow hydroxyapatite (HA) microspheres (106–150 μm) in the form of three-dimensional (3D) scaffolds or individual (loose) microspheres were created using a glass conversion process. The capacity of the implants, with or without transforming growth factor- 1 (TGF- 1), to regenerate bone in a rat calvarial defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 34 publications
(38 reference statements)
1
29
1
Order By: Relevance
“…Our more recent work showed that loading the hollow HA microspheres with transforming growth factor beta 1 (TGFβ1) (5 μg/defect) can enhance bone regeneration in rat calvarial defects at 6 weeks but not at 12 weeks [15]. However, the amount of new bone formed in the defects implanted with the TGF-loaded microspheres was only ~20% of the total defect area after 6 or 12 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Our more recent work showed that loading the hollow HA microspheres with transforming growth factor beta 1 (TGFβ1) (5 μg/defect) can enhance bone regeneration in rat calvarial defects at 6 weeks but not at 12 weeks [15]. However, the amount of new bone formed in the defects implanted with the TGF-loaded microspheres was only ~20% of the total defect area after 6 or 12 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…2,8,15,18 Our process, based on a parallelepipedic cell culture chamber and a CP granule monolayer, was thus efficient enough to promote the differentiation of the MC3T3 subclone 4 cells. It has been shown that the use of additional growth factors, such as transforming growth factor beta, bone morphogenetic protein, or fibroblast growth factors, may create complications during the clinical step, 55 with the need for accurate and precautionary validation for the patient's safety.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] Various materials have been studied and considered as possible scaffolds for in vitro bone ingrowth, such as ceramics, 10,11 polymers, 12,13 natural biomaterials such as silk or chitosan [14][15][16] or to a lesser extent metals, 7 and composites of these different groups. 17 Relevant shapes for the scaffold have also been debated, with different studies on granules and microspheres, 18 fibres, 19,20 hydrogels, 21 or engineered complex structures. 22,23 In addition, a bioreactor's ability to mimic in vivo environmental conditions is still an unsolved issue, with a wide variety of systems using mechanical stretching, flow perfusion, spinner flasks, rotating wall vessels, [24][25][26] or specifically designed chambers.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of biological molecules including carbohydrates, extracellular matrix (ECM) proteins or their components, e.g. arginine-glycine-aspartic acid (RGD) peptides and growth factors have been considered to elicit specific cellular responses, increase the interaction between the cells, material surfaces and tissues, and thereby result in integration and tissue regeneration [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%